Hausa vernacular architectural style of early Mosque buildings: A case stuy of Yandoka Street Moswue, JOS - M. M. Bello; Adekoyejo Babatunde Jolaoso; N. A. Umaru; S. T. Adamu (Program Studi Arsitektur Fakultas Teknik Universitas Katolik Widya Mandira, 2023)
This paper investigates the impact of modern and contemporary trends on an eighty-seven years’ old mosque in Jos built in the typical Hausa Vernacular Architectural style, as well as the extent to which its vernacular features have been lost and/or retained. The study focused on selected architectural features which do not essentially affects the performance of the primary mosque's functions. A qualitative survey was adopted using case study approach and complemented with content analysis of related literature reviewed to extract information on the challenges of restoration and preservation or conservation of the key features of traditional Hausa Architecture on the Mosque buildings in the study area of Jos, Plateau State, Nigeria from the randomly selected traditional/indigenous builders and practicing architects. The Yandoka Street Mosque was purposively selected as a case study, because of its historical antecedence, religious and communal attachment, as well as its socio-political and cultural relevance in the study area. Information was collected using the unobtrusive observation method and were descriptively presented in the form of layout plan, material deduction, construction techniques and technology adopted for the mosque’s construction. Findings shows that, the influence of the identified key factors have become a threatening phenomenon to the survival of the preservation and conservation historical values and heritages of Hausa mosque architectural style. The paper advocates preservation and conservation of the original mosque architectural style from the point of view of sustainability and made recommendations towards the preservation, development and execution of strategies for branding, national identity and protection of value systems for the public good